PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA RUMAH PENDIDIKAN BIMBA AIUEO KOTA SURABAYA - Shafira, Lintang (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Constructive to others to make a cooperative effort to achieve the planned goals. As an explanation in carrying out daily leadership tasks within a professional management framework. The aim of this research is to determine the effect of leadership style on employee performance with work motivation. This study uses a quantitative approach. The object of this research is the employees of the Surabaya BiMBA (Tutoring Tutoring) house. There is a positive and significant influence between leadership style on work motivation, and there is a positive and significant influence of work motivation on employee performance. The higher the work motivation, the more employee performance will increase. The results of this research show that leadership style and organizational culture have a positive and significant effect on motivation. Organizational culture and motivation have a positive and significant effect on employee performance. Organizational culture has a positive and significant effect on employee performance through motivation variables.